Loss of COX4I1 Leads to Combined Respiratory Chain Deficiency and Impaired Mitochondrial Protein Synthesis - Čunátová, Kristýna; Reguera, David Pajuelo; Vrbacký, Marek; Fernández-Vizarra, Erika; Ding, Shujing; Fearnley, Ian M; Zeviani, Massimo; Houštěk, Josef; Mráček, Tomáš; Pecina, Petr (Cells, 2021)
The oxidative phosphorylation (OXPHOS) system localized in the inner mitochondrial membrane secures production of the majority of ATP in mammalian organisms. Individual OXPHOS complexes form supramolecular assemblies termed supercomplexes. The complexes are linked not only by their function but also by interdependency of individual complex biogenesis or maintenance. For instance, cytochrome c oxidase (cIV) or cytochrome bc1 complex (cIII) deficiencies affect the level of fully assembled NADH dehydrogenase (cI) in monomeric as well as supercomplex forms. It was hypothesized that cI is affected at the level of enzyme assembly as well as at the level of cI stability and maintenance. However, the true nature of interdependency between cI and cIV is not fully understood yet. We used a HEK293 cellular model where the COX4 subunit was completely knocked out, serving as an ideal system to study interdependency of cI and cIV, as early phases of cIV assembly process were disrupted. Total absence of cIV was accompanied by profound deficiency of cI, documented by decrease in the levels of cI subunits and significantly reduced amount of assembled cI. Supercomplexes assembled from cI, cIII, and cIV were missing in COX4I1 knock-out (KO) due to loss of cIV and decrease in cI amount. Pulse-chase metabolic labeling of mitochondrial DNA (mtDNA)-encoded proteins uncovered a decrease in the translation of cIV and cI subunits. Moreover, partial impairment of mitochondrial protein synthesis correlated with decreased content of mitochondrial ribosomal proteins. In addition, complexome profiling revealed accumulation of cI assembly intermediates, indicating that cI biogenesis, rather than stability, was affected. We propose that attenuation of mitochondrial protein synthesis caused by cIV deficiency represents one of the mechanisms, which may impair biogenesis of cI.
Keywords: biogenesis interdependency; Glycolysis; OXPHOS; Electron Transport Complex IV; HEK293 Cells; mitochondrial protein synthesis; spotřeba kyslíku; Oxygen Consumption; COX4; complex I; mitochondria; podjednotky proteinů; Mitochondrial Diseases; oxidativní fosforylace; proteosyntéza; Protein Biosynthesis; cIV assembly; Oxidative Phosphorylation; Mitochondrial Proteins; HEK293 buňky; Humans; glykolýza; cIV; complexome profiling; Protein Subunits; knock-out; COX; mitochondriální proteiny; respirační komplex IV; lidé; cI; mitochondriální nemoci